The influence of interdental spacing on the detection of proximal caries lesions in primary teeth - Tatiane Fernandes Novaes; Ronilza Matos; Paula Celiberti; Mariana Minatel Braga; Fausto Medeiros Mendes (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The aim of this study was to investigate the influence of interdental spacing on the performance of proximal caries detection methods in primary molars. In addition, aspects related to temporary tooth separation with orthodontic separators were evaluated. The proximal spaces between the posterior primary teeth (n = 344) of 76 children (4-12 years old) were evaluated before and after temporary separation. Stainless steel strips with different standardized thicknesses were used to measure the presence of biological spacing and the spacing obtained after temporary separation with orthodontic rubber rings. First, the presence of proximal caries lesions was assessed by visual inspection, bitewing radiographs and a pen-type laser fluorescence device (DIAGNOdent pen). Visual inspection after temporary separation with separators was the reference standard method in checking the actual presence of caries. Multilevel analyses were performed considering different outcomes: the performance of the methods in detecting caries lesions and the spacing after temporary separation. The spacing did not influence the performance of the caries detection methods. The maximum spacing obtained with temporary tooth separation was 0.80 mm (mean ± standard deviation = 0.46 ± 0.13 mm). The temporary separation was more effective in the upper arch and less effective when an initial biological interdental spacing was present. The biological interdental spacing does not influence the performance of proximal caries detection methods in primary molars, and temporary tooth separation provides spacing narrower than 1.0 mm.